Contributions of ordinary citizens towards development of a society: the case of Bangladesh - Hossain, Ishtiaq (LifeScience Global, 2015)
This paper highlights the contributions of ordinary citizens to the development of a developing country – Bangladesh. The article discusses the contributions made by two ordinary citizens of Bangladesh, Begum Rokeya Sakhawat Hossain and Khondker Azizur Rahman Salim, toward building the society. It is argued in this paper that the participation of ordinary citizens in the development of a society is important. While the elites of a society may lay down the strategy, and sometimes the policies for developing such a society, ordinary citizens on their own can, in fact, play an important role in those regards. This paper highlights the strategies adopted by those two common citizens. It also chronicles their sufferings, sacrifices and achievements. The paper concludes that while the contributions made by Begum Rokeya Sakhawat Hossain is celebrated, those of Khondker Azizur Rahman Salim remains unrecognised by the Bangladesh society. The paper adopts qualitative research method. Information about Begum Rokeya Sakhawat Hossain have been collected from works done by her and by others on her. Khondker Azizur Rahman was interviewed both in Dhaka, Bangladesh and Maryland, the United States, where he currently lives.